Azoximer Bromide: Mystery, Serendipity, and Promise - Grivtsova, Lyudmila Yuryevna; Falaleeva, Natalia Alexandrovna; Tupitsyn, Nikolay Nikolaevich (Frontiers in Oncology, 2021)
Azoximer bromide (AZB) was identified as an immunomodulator, and was initially developed and currently successfully indicated as one of several natural polyelectrolytes, a vaccine adjuvant, and an effective agent for the treatment of infectious and inflammatory diseases of viral, bacterial, and fungal origin. AZB has the potential to increase an individual’s resistance to local and general infection and is indicated for the treatment of viral infections, and has also demonstrated clinical efficacy in the treatment of a variety of secondary immunodeficiencies. However, AZB may offer long-term promise beyond use against infection. Multiple clinical trials and research studies in cancer patients have reported favourable outcomes with AZB as well as an optimal safety and tolerability profile. The findings raise the possibility of direct antitumor properties. This literature review analyses the novel mechanisms that mediate the AZB direct anticancer effects. Overall, the evidence suggests that AZB has the hallmark of an agent that could be used to support existing cancer treatments at different stages of disease.